WEB 2.0 Technologies Supporting Students and Scholars in Higher Education - Paula Miranda; Isaías, P.; Costa, C.; Pifano, S. (Lecture Notes in Computer Science, 2013)
As computers, notebooks and mobile phones update Facebook’s statuses, search and contribute to different themes for Wikipedia and tweet the latest news, a generation and a unique manner of communication are born from this new terminology and philosophy of open and flexible access, shared knowledge, user-generated content and media richness. As many trends, Web 2.0 started by being an exclusivity of certain type of users and then a snowball-like effect made it one of the most popular techno-social phenomena of the 21st century. Word of mouth, user recommendation and the technology itself turned an innovation into a routine. Soon it was disseminated through the different sectors of society, reaching business, health and also education. This paper will examine the benefits that both students and scholars experience in using Web 2.0 in the higher education context.